PENGUJIAN VALIDITAS EMPIRIS CAPITAL ASSET PRICING MODEL DI PASAR MODAL INDONESIA - Simangunsong, Yolanda Marsyella; Wirama, Dewa Gede (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 9 No 1 (2014), 2014)
ABSTRACT A careful analysis of securities trading, supported by thorough and accurate data needed to determine the level of returns and risks in investing. The global financial crisis led many academics to question the validity of market efficiency and the Capital Asset Pricing Model which is one of the estimation model that can determine the return and risk relationship. This study aimed to test the empirical validity of Capital Asset Pricing Model in Indonesian capital market. This study used a quantitative approach with 45 firms as sample (270 observations) which were incorporated on LQ45 stock index in the period of August 2012 until January 2013. Simple linear regression analysis was conducted to obtain an overview of the relationship between beta and return. The analysis showed that beta did not explain return. In addition, four other predictions that were used to empirically test the Capital Asset Pricing Model could not be fulfilled. This meant that the Capital Asset Pricing Model was not valid in the Indonesian capital market. Keywords: beta,CAPM, LQ45, return